2012
DOI: 10.1212/wnl.0b013e3182703fd2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective lifestyles and the aging brain

Abstract: In this large, narrow-age sample of adults in their 70s, physical activity was associated with less atrophy and WML. Its role as a potential neuroprotective factor is supported; however, the direction of causation is unclear from this observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
154
3
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(176 citation statements)
references
References 37 publications
15
154
3
4
Order By: Relevance
“…95 The brain renin-angiotensin II system and hypertension in SHR are reported to be attenuated by exercise, 96 which preserves small vessel function and is associated with fewer WMH. 97 Angiotensin receptor blockers and exercise are also expected to improve large artery remodeling. 98 Thus, the recent advancement in the understanding of SVD risk factors and related molecular pathways from animal and human studies may provide clues in the search for potential remedies for SVD (Figure 3).…”
Section: Future Perspectives In the Treatment Of Svdmentioning
confidence: 99%
“…95 The brain renin-angiotensin II system and hypertension in SHR are reported to be attenuated by exercise, 96 which preserves small vessel function and is associated with fewer WMH. 97 Angiotensin receptor blockers and exercise are also expected to improve large artery remodeling. 98 Thus, the recent advancement in the understanding of SVD risk factors and related molecular pathways from animal and human studies may provide clues in the search for potential remedies for SVD (Figure 3).…”
Section: Future Perspectives In the Treatment Of Svdmentioning
confidence: 99%
“…Research in the past decade has identified some factors that modulate the decline and enhance its integrity in healthy older adults, including physical exercise (Fleischman et al, 2015;Gow et al, 2012;Sen et al, 2012), cognitive activities (Wirth, Haase, Villeneuve, Vogel, & Jagust, 2014), and complex leisure activities (Saczynski et al, 2008). In one study, older adults who participated in a life-long high volume and high-intensity exercise training showed a significant 83% reduction in deep white matter lesions and a 44% reduction in total white matter hyperintensities volume relative to their sedentary counterparts.…”
Section: Wml and White Matter Plasticitymentioning
confidence: 99%
“…9,10 Both animal and human studies 11 suggest that the benefit of physical activity on brain health in aging may be at least partially attributable to enhancement of blood flow, angiogenesis, and maintenance of the cerebral vasculature 12 and a concomitant reduction of WMH burden. 13 These studies suggest that higher levels of physical activity in older adults may provide some degree of protection from the untoward consequences of accumulating brain pathology on motor function in older age.…”
mentioning
confidence: 92%